2020
DOI: 10.3390/antiox9100915
|View full text |Cite
|
Sign up to set email alerts
|

Sex and SP-A2 Dependent NAD(H) Redox Alterations in Mouse Alveolar Macrophages in Response to Ozone Exposure: Potential Implications for COVID-19

Abstract: Co-enzyme nicotinamide adenine dinucleotide (NAD(H)) redox plays a key role in macrophage function. Surfactant protein (SP-) A modulates the functions of alveolar macrophages (AM) and ozone (O3) exposure in the presence or absence of SP-A and reduces mouse survival in a sex-dependent manner. It is unclear whether and how NAD(H) redox status plays a role in the innate immune response in a sex-dependent manner. We investigated the NAD(H) redox status of AM from SP-A2 and SP-A knockout (KO) mice in response to O3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 92 publications
3
28
0
Order By: Relevance
“…We have previously shown that at 18 h post-O 3 exposure, the level of SOD2 mRNA was decreased in SP-A2 males, whereas, in KO, both SOD2 and CAT were significantly increased, indicating that SP-A2 may play a role in the homeostasis of ROS [ 39 ]. In fact, our recent studies indicate that SP-A2 contributes/regulates the NAD(H) redox status in a sex-dependent manner [ 106 ]. Thus, the observed FOXO1 upregulation may be a mechanism that alleviates the ROS impact on AM cells of male SP-A2 and co-ex compared to females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that at 18 h post-O 3 exposure, the level of SOD2 mRNA was decreased in SP-A2 males, whereas, in KO, both SOD2 and CAT were significantly increased, indicating that SP-A2 may play a role in the homeostasis of ROS [ 39 ]. In fact, our recent studies indicate that SP-A2 contributes/regulates the NAD(H) redox status in a sex-dependent manner [ 106 ]. Thus, the observed FOXO1 upregulation may be a mechanism that alleviates the ROS impact on AM cells of male SP-A2 and co-ex compared to females.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to SP-A2 males, where the cell cycle pathway was not detected at the 4 h time point but instead, the ROS homeostasis pathway was identified as playing a role [ 39 ]. One may postulate that in the absence of SP-A1, SP-A2 alone at the 4 h post-O 3 time point affects ROS-related mechanisms and one of these mechanisms may be via its ability to regulate the NAD(H) redox status [ 106 ]. However, at a later time point (18 h), SP-A2 shifts to recovery mechanisms by perhaps activating the cell cycle, growth, and proliferation pathway (present study).…”
Section: Overall Commentsmentioning
confidence: 99%
“…The optical redox ratio Fp/(NADH + Fp) linearly correlates with the NAD + /(NADH + NAD + ) ratio that is determined using liquid chromatography–mass spectrometry and reflects the mitochondrial redox state [ 94 , 95 ]. A higher Fp or lower NADH or higher optical redox ratio corresponds to a higher mitochondrial ROS level; either oxidative or reductive extreme correlates with a higher ROS level [ 48 , 96 ] and a more oxidized redox state (a higher redox ratio) is associated with neurodegeneration [ 97 , 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tile images (pixel size 1.172 Ă— 1.172 µm 2 ) were taken using a 5Ă—/0.16 NA objective with shading correction on the fly, followed by photostitching. The acquired images were processed with a customized Matlab ® (The MathWorks, Inc., 1 Apple Hill Dr, Natick, MA 01760, USA) routine to generate the redox images where the redox ratio Fp/(NADH + Fp) image was generated pixel-by-pixel from the NADH and Fp images and to obtain the mean value of each of the redox indices (NADH, Fp, the redox ratio) using global averaging [ 47 , 48 , 49 ]. Obvious fluorescent artifacts (in either channel) were removed during the imaging analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The bronchoalveolar lavage fluid was placed on ice and shipped within ~2.5 h to the remote site for imaging analysis. We found ozone exposure shifted NAD(H) to a more oxidized redox status in these freshly isolated AM compared to controls [ 5 ]. In the present study we used the same technique to investigate and compare the NAD(H) redox status of cryopreserved AM to that of fresh cells with a lag time on ice prior to experimentation which we previously published [ 5 ].…”
Section: Introductionmentioning
confidence: 99%